Milk wars: Cooperation, contestation, conflict and the Irish War of Independence - Eoin McLaughlin; Paul Sharp; Christian Volmar Skovsgaard; Christian Vedel (European Historical Economics Society (EHES), 2024)
Agricultural cooperation is seen as a way to solve collective action problems and has been associated with high social capital and other beneficial impacts in the countryside beyond productivity increases. But what if it comes into conflict with existing private concerns? The Irish dairy cooperatives from the 1890s entered a contested market for milk, and soon became associated with various degrees of conflict: legal disputes and physical violence. We hypothesize that this led to poor social capital, manifesting in conflict during the Irish War of Independence. We analyze novel data on cooperative and private creameries, as well as measures of conflict. Our findings indicate a significant positive correlation between the presence of cooperatives and local conflict intensities, persisting even after controlling for various confounders. An instrumental variable approach based on prior specialization in dairying validates this. Cooperation might thus both reflect social capital but also have pernicious impacts on it.
Keywords: N53; N54; Q13; Z13; 330; Ireland; Cooperatives; Social Capital; Market Contestation